JURIDICAL STUDIES MASTERY MINE CONCEPT IN THE APPROACH TO HISTORY AND PRINCIPLES OF IMS (INTERNASIONAL MINIMUM STANDARD OF CIVILIZATION) - Recca Ayu Hapsari (UBL, 2016)
Article 33 (3) of the 1945 constitution state that “the land, the water and the nature riches contained there in shall be controlled by the state and exploited to the greatest benefit of the people”. As Stuart G Gross that article 33 (3) goes beyond traditional affirmation articulating, rather, a fundamental, inviolable precept of Indonesian constitutional law. Thus, contracts of the work (CoWs) resemble traditional concession contract only some ways, such as the manner in which revenue is transferred back to the state in the form of taxation and royalties and the level of control holders of CoWs have over operation. However, in the important ways foreign mining companies act not as concessionaires but as contractors for republic of Indonesia, which retains title to unextracted minerals and for whom the mining companies work.